DESIGN OF METAL HEAT CONDUCTIVITY MEASUREMENT USING PROBE METHOD - Fitria Hidayanti; Hari Hadi Santoso; Gigih Baskara (Program Studi Fisika Universitas Negeri Jakarta, 2020)
This study aims to design a tool that can measure the heat conductivity of metals by the Probe method. The design method was used by using a heat-flowed metal beam and the use of an LM35 temperature sensor to measure temperature changes on the probe. We are designing a measurement system based on conduction heat transfer. The metal used in the design is aluminum and carbon steel. For each metal tested, an LM35 temperature sensor is placed on the metal to find out that a temperature change has occurred. The conductivity value can be obtained from the temperature difference between the probe and the metal being tested, the temperature change of the probe, the temperature change of the metal being tested, and the heating time. This value is processed and calculated by the microcontroller into the value of heat conductivity. The measurement results show that the average heat conductivity value is 214.93 W/moC for aluminum and 53.81 W/moC for carbon steel.